Prevalence of Major Depressive Disorder in Patients Following Spine Trauma - Abbas, Amber; Jan, M. Imran; Ali, Farhad; Kumar, Ramesh; Anis, Zulqarnain; Khulsai, Sameer (Biological and Clinical Sciences Research Journal, 2025)
Spinal trauma carries a high risk of psychological sequelae, yet Pakistani data are scarce. Objectives: To measure the prevalence of probable Major Depressive Disorder (MDD) ≥6 weeks after injury and explore associated factors. Methods: A descriptive cross‑sectional study was conducted in the spine outpatient department of SMBBIT, Karachi, from August 2024 to January 2025. The institutional review board approved the protocol, and written informed consent was obtained from all participants prior to their participation. Consecutive sampling was used. Inclusion criteria were: adults aged 18–65 years; documented vertebral fracture or dislocation confirmed on imaging; presentation ≥6 weeks after injury; and ability to understand Urdu. Exclusion criteria comprised congenital spinal deformity, tumour, prior spine surgery, active psychosis, previous psychiatric diagnosis, or use of antidepressants before trauma. A PHQ-9 score≥10 indicated MDD; Wilson confidence intervals and bivariate tests summarized the results. Results: MDD prevalence was 42.6 % (95 % CI 34.9–50.6); female sex and comorbidity were significant correlates. Conclusions: One‑third of survivors screened positive, underscoring the need for integrated mental‑health Care.